Numerical Investigation of Turbulent Heat Transfer Properties at Low Prandtl Number - Chai, Xiang; Liu, Xiaojing; Xiong, Jinbiao; Cheng, Xu (Frontiers in Energy Research, 2020)
The sodium-cooled fast reactor (SFR), which is one of the most promising candidates for meeting the goal declared by the Generation IV International Forum (GIF), has drawn a lot of attention. Turbulent heat transfer in liquid sodium, which is a low-Prandtl fluid, is an extremely complex phenomenon. The limitations of the commonly used eddy diffusivity approach have become more evident when considering low-Prandtl fluids. The current study focuses on the assessment and optimization of the existing modeling closure for single-phase turbulence in liquid sodium based on reference results provided by the LES method. In this study, a wall-resolved Large-Eddy Simulation was performed to simulate the flow and heat transfer properties in a turbulent channel at low Prandtl number. The simulation results were first compared with the DNS results obtained from the literature. A good agreement demonstrated the capability of the employed numerical approach to predict the turbulent and heat transfer properties in a low-Prandtl number fluid. Consequently, new reference results were obtained for the typical Prandtl number and wall heat flux of an SFR. A time-averaged process was employed to evaluate the temperature profile quantitatively as well as the turbulent heat flux. Their dependency was also evaluated based on a systematic CFD simulation that covers the typical Reynolds numbers of SFRs. Based on the reference results obtained, the coefficients employed in an algebraic turbulent heat flux model (AFM) are calibrated. The optimized coefficients provide more accurate prediction of heat transfer properties for typical flow conditions of an SFR than the existing models found in the literature.